2012
DOI: 10.1159/000343998
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging on Acoustic Parameters of Voice

Abstract: Background/Aims: There are no studies of the phonatory parameters of elderly Iranian speakers. The purpose of this study was to obtain normative acoustic data for a group of elderly Iranian male and female speakers over 70 years of age. Four selected acoustic parameters [fundamental frequency (F0), jitter, shimmer, and harmonics-to-noise ratio] were obtained and compared to a group of young and middle-aged speakers. Methods: Subjects were 21 Iranian elderly men and 20 Iranian elderly women. The age range for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
55
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 54 publications
10
55
2
1
Order By: Relevance
“…Finally, it can be observed that the periodicity in the Control set was found to be lower than in the TTS set. This decrease is due to aging, as known from the literature (Dehgan and Scherer, 2013). Note that all these results derived from the use of the SRH algorithm have been corroborated by a visual inspection of the signal.…”
Section: Periodicity Of the Speech Signalsupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, it can be observed that the periodicity in the Control set was found to be lower than in the TTS set. This decrease is due to aging, as known from the literature (Dehgan and Scherer, 2013). Note that all these results derived from the use of the SRH algorithm have been corroborated by a visual inspection of the signal.…”
Section: Periodicity Of the Speech Signalsupporting
confidence: 78%
“…However, the differences between the Control and TE voices did not turn out to be significant. One possible explanation is the fact that elderly normophonic voices are known to already exhibit a certain harshness (Dehgan and Scherer, 2013).…”
Section: Periodicity Of the Speech Signalmentioning
confidence: 99%
“…These changes have an impact on voice production and quality (Mazzetto de Menezes et al 2014). Indeed, aging negatively affects voice stability and amplitude in a sex-dependent manner (Linville and Fisher 1985;Ma and Love 2010;Dehqan et al 2013;Goy et al 2013). For instance, men generally show a gradual increase in fundamental frequency (f0) with age (Honjo and Isshiki 1980;Harnsberger et al 2008;Torre and Barlow 2009;Ma and Love 2010;Dehqan et al 2013), while women exhibit a decrease in f0 with age (Honjo and Isshiki 1980;Torre and Barlow 2009;Ma and Love 2010;Da Silva et al 2011;Dehqan et al 2013;Goy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report an amplitude decrease for both women and men Da Silva et al 2011), while other show it only for men (Morris and Brown 1994;Goy et al 2013). The effect of age on voice perturbation measures is less clear: while some studies have shown that voice stability defined as jitter and shimmer declines with age (Wilcox and Horii 1980;Baken 2005;Dehqan et al 2013), other studies did not find significant changes with age Goy et al 2013). Finally, while some studies have reported reduced maximum phonation time (MPT) in aging (Ptacek et al 1966;Kreul 1972), recent reports observed no significant decrease in MPT values in older participants (Maslan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it can be observed that the periodicity in the Control set was found to be lower than in the TTS set. This decrease is due to aging, as known from the literature [11]. …”
Section: Periodicity Of the Speech Signalmentioning
confidence: 76%